Fe Incorporation in Ni-Based Layered Hydroxides: Implications for Oxygen Evolution Electrocatalysis - Jaramillo Hernández, Camilo (2025)
Alkaline water electrolysis (AWE) is a promising hydrogen production method but faces challenges with the sluggish oxygen evolution reaction (OER), which requires high voltages. Nickel-based layered hydroxides (LHs) are effective earth-abundant OER catalysts, though Fe incorporation from electrolyte impurities significantly enhances their performance. This study systematically examines Fe impurity incorporation in Ni-based LH phases: α-Ni-LH, β-Ni-LH, and NiAl- and NiFe-layered double hydroxides (LDHs). Two incorporation methods were explored: a standard electrolyte purification process and an electrochemical activation approach. Electrochemical activation is more effective, and expanded phases have more affinity to allocate Fe. Incorporation experiments suggest a partial transformation of NiAl into NiFe-like LDH, which exhibits a superior electrocatalytic performance. Spectroscopical techniques suggest that the Fe incorporated in the NiAl LDH could be structural due to synergy with the concomitant leaching of Al in the electrolyte. For pristine NiFe-LDH, these treatment strategies proved ineffective, suggesting that such approaches are unsuitable for optimized compositions. Furthermore, the process is highly dependent on the Fe impurity concentration in the electrolyte. This work highlights the role of the initial LH phase in determining structural Fe incorporation, providing insights for designing efficient electrodes in AWE. It also emphasizes the need for strict control of the electrolyte to optimize catalyst performance.